Optimal Morse – Smale flows with singularities on the boundary of surface - Prishlyak, A.O.; Loseva, M.V. (Нелінійні коливання, 2018)
We consider optimal flows on noncompact surfaces with boundary, which have a minimum number of
fixed points and all of them lie on the boundary of the surface. It is proved that the flow will be optimal if
it has a single sink and a single source. The structure of optimal flows on simply connected region, Mobius ¨
strip, torus with a hole and Klein bottle with a hole are described. Розглядаються оптимальнi потоки на компактних поверхнях з межею, у яких мiнiмальне число
нерухомих точок i всi вони лежать на межi поверхнi. Доведено, що потiк буде оптимальним, якщо
вiн має єдиний стiк i єдиний витiк. Описано структуру всiх оптимальних потокiв на однозв’язнiй
областi, листi Мьобiуса, торi з дiркою та пляшцi Клейна з дiркою.